On-station characterisation of indigenous Menz and Horro sheep breeds in the central highlands of Ethiopia - Tibbo, Markos; Ayalew, W.; Awgichew, K.; Ermias, E.; Rege, J.E.O. (Cambridge University Press, 2004)
On-station characterisation of indigenous Menz (n = 1639) and Horro (n = 1135) sheep of Ethiopia in the central highlands of the country was undertaken between 1992 and 1997 at the Debre Berhan Research Station of the International Livestock Research Institute (ILRI) to study the phenotypic characteristics of the breeds. Body weights, linear body measurements, and testicular parameters were studied. The traits studied were live body weights (LWT), body length (BL), heart girth (HG), height at withers (WH), pelvic width (PW), chest depth (CD), distance between last rib and tuber coxae (DLP-ATR), scrotal circumference (SC), testicular diameter (TD), testicular length (TL), and epididymal tail diameter (ED). All except LWT (which was also measured at birth) were measured at 3, 12 and 24 months age. Fixed effects included in the analyses were breed, sex, birth type, birth season, birth year, and significant first-order interactions. The Horro sheep had significantly (P<0.05) larger LWT at all ages than the Menz by as much as 6 to 18%. In both breeds, lambs born single were significantly (P<0.05) heavier than those born as twins or triplets. In all age categories and both breeds, males were consistently heavier and larger in size than females. Except for lambs of 3 months of age, the Horro sheep had larger (at least P<0.05) testicular measurements than Menz for all age categories.